The Effects of Cognitive and Focus on Form Instruction toward Efl Learners’ Achievement of Grammar in Vocational School At SMKN 3 Kota Serang - Cucum Rohmawati; Yudi Juniardi (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2018)
The objective of this research is to find out the effect of cognitive and focus on form instruction toward vocational high school EFL learners’ achievement of grammar in vocational school at SMKN 3 Kota Serang. The researcher used quantitative research implementing the true experimental design as research method. There were two groups used in this research, the mainly; the experimental and control group. Sample of this research is students of SMKN 3 Kota Serang, 39 students selected for experimental group, and 38 students selected for control group. The research found that there is significant influence of cognitive and focus on form instruction toward vocational high school EFL learners’ achievement of grammar, it was indicated by the value of t-test higher than the value of t-table (0.950 > 0.000) at the level of significant of α 0.05 and the degree of freedom of 75. It means that the hypothesis was accepted. From those findings, it can be concluded that the use of cognitive and focus on form instruction is effective to influence learners’ achievement of grammar in vocational school at SMKN 3 Kota Serang. All these suggest that the use of cognitive and focus on form instruction in the class of English is highly encouraged.